Comparison of platelet count by manual and automated method - Jain, Dileep Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Since the emergence of dengue fever in the past few years, platelet count has become a routine test in every pathology lab. Common methods are by peripheral blood smears made from blood collected in ethylenediaminetetraacetic acid (EDTA) tubes, by neubaeur chamber, automated method by hematology cell counter. Methods: Blood samples of 460 adult patients and 72 children (<15 years), including indoor and outdoor, between May to August 2019, attending Hind institute of medical sciences, were collected in EDTA tubes. Samples were properly mixed on blood shaker and immediately peripheral blood smears were made and stained with Leishman stain. Platelet count of every sample was done by peripheral blood smear and by Mindray (BC5150) automated cell counter, simultaneously. Results: Results by manual slide method are slightly higher than automated method but significantly not different from automated method. Conclusions: Traditional slide method can also be used if done carefully comparable to automated method especially useful in small labs which can’t afford automated cell counter.